1984
DOI: 10.1161/01.str.15.4.635
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow and oxygen consumption in human aging.

Abstract: SUMMARY The oxygen-15 continuous inhalation technique and PET were used to study the age-related changes in regional CBF and CMRO 2 . Twenty-seven patients, aged 19 to 76 years, free of any history of cerebral disease and vascular risk factors were examined in "resting state." CBF, CMRO 2 and oxygen extraction fraction (OEF) values were calculated in seven different brain structures as well as in mean gray matter. Left-right ratios were also computed for all symmetrical structures analyzed.Mean gray CBF, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
172
2
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(210 citation statements)
references
References 37 publications
35
172
2
1
Order By: Relevance
“…Overall, our findings are compatible with the results of studies using a variety of neuroimaging modalities that aging is especially associated with structural, metabolic, and neurochemical changes in regions of the prefrontal cortex (Pantano et al, 1984;Riege et al, 1985;Waldemar et al, 1991), the striatum (Murphy et al, 1992;Riege et al, 1985;Rinne et al, 1993;Sawle et al, 1990;van Dyck et al, 1995), and also the temporal lobes (Arrigada et al, 1992;Loessner et al, 1995;Pantano et al, 1984;Price et al, 1991). This position is not very different from that reached by West (1996), after a comprehensive review of the available neurobiological evidence.…”
Section: Relevance To Neural Theories Of Agingsupporting
confidence: 90%
“…Overall, our findings are compatible with the results of studies using a variety of neuroimaging modalities that aging is especially associated with structural, metabolic, and neurochemical changes in regions of the prefrontal cortex (Pantano et al, 1984;Riege et al, 1985;Waldemar et al, 1991), the striatum (Murphy et al, 1992;Riege et al, 1985;Rinne et al, 1993;Sawle et al, 1990;van Dyck et al, 1995), and also the temporal lobes (Arrigada et al, 1992;Loessner et al, 1995;Pantano et al, 1984;Price et al, 1991). This position is not very different from that reached by West (1996), after a comprehensive review of the available neurobiological evidence.…”
Section: Relevance To Neural Theories Of Agingsupporting
confidence: 90%
“…The observed decline of the GM-WM contrast (CBV GM /CBV WM and CBF GM /CBF WM ) with age has been reported previously (1). In comparison to literature values from different modalities ( 15 O PET, Xe CT, DSC-MRI, T 1 -weighted MRI, I CT) (1,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), which provide CBV and CBF values listed in Table 2, roughly, a factor 4 overestimation is observed.…”
Section: Cbv and Cbf In Gray/white Mattersupporting
confidence: 75%
“…Many methods, including the nitrous oxide, 23 133 xenon (Xe)-single-photon emission CT (SPECT), 9,17 Xe-CT, 24 positron-emission tomography (PET) 25,26 dynamic MR, 25,27 and perfusion CT, 24 have been used to measure the regional CBF. In most studies, 9,17,[23][24][25][26][27] CBF values were reported in terms of milliliters per 100 grams of brain tissue per minute, and in some studies CBFs were determined separately for white and gray matter.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, 9,17,[23][24][25][26][27] CBF values were reported in terms of milliliters per 100 grams of brain tissue per minute, and in some studies CBFs were determined separately for white and gray matter. In a study of the effect of age on the total CBF using nongated 2D PC MRA, 5 a factor of 10.81-12.14 was used in the correlation between the total CBF (milliliters per minute) from the 2D PC MRA and the total CBF (milliliters per minute 100 grams) from the nitrous oxide, 133 Xe-SPECT, Xe-CT, and PET.…”
Section: Discussionmentioning
confidence: 99%